A study on the students' perception of administrative service quality: a case of UiTM Kedah and Perlis / Jamaludin Akbar...[et al.] - Akbar, Jamaludin; Khamis, Muhammad Sazri; Mansor, Kamarul Ariffin (2006)
This study sets out to look at the issues concerning service quality of administrative staff in UiTM Kedah and Perlis from student perspective The issues being looked into cover to what extent are the UiTM Kedah and Perlis meeting the expectations of their diploma student , whether any discrepancies exist in the expectations and perceptions of students against different departments (clinic , library, security , college , academic affairs , and student affairs) and also try to find out what are the most important determinants of overall service quality (empathy , assurance, responsiveness , reliability, and tangible) in UiTM Kedah and Perlis . Data gathered through questionnaires correspond to the issues and the findings showed that al l six departments in UiTM Kedah and Perlis have failed to meet the expectations of diploma students . Clinic and library are two departments that close to meet students' expectation in UiTM Kedah and Perlis . Results also showed that for Kedah branch , three dimensions namely assurance, empathy, and reliability found to be an important determinant of service quality while for Perlis branch four dimensions namely assurance, responsiveness , empathy, and tangible are found to be an important detem_i,1 ant of service quality. The recommendations for this study are also included for further research and use . xi